2017
DOI: 10.1126/sciadv.1601631
|View full text |Cite
|
Sign up to set email alerts
|

Key role of the dopamine D 4 receptor in the modulation of corticostriatal glutamatergic neurotransmission

Abstract: The function of the dopamine D4 receptor and the product of a clinically significant gene polymorphic variant is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 30 publications
2
75
0
Order By: Relevance
“…21,22 In the present study, we aimed at a more motor-involved striatal area, the dorsal striatal area that receives innervation from the agranular motor cortex (Fig 1A). This corticostriatal projection has been anatomically well defined from different studies analyzing striatal neuronal activation upon cortical-electrical stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…21,22 In the present study, we aimed at a more motor-involved striatal area, the dorsal striatal area that receives innervation from the agranular motor cortex (Fig 1A). This corticostriatal projection has been anatomically well defined from different studies analyzing striatal neuronal activation upon cortical-electrical stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 It could then be demonstrated that adenosine A 2A receptors (A2AR) play a strong facilitatory role, since perfusion through the microdialysis probe of the selective A2AR antagonist MSX-3, completely counteracted optogenetically-induced corticostriatal glutamate release. 21 In agreement with a functional upregulation of A2AR being involved with the increased sensitivity of corticostriatal terminals induced by BID (see Discussion and refs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific subtype of EAA receptor activated was crucial to the direction of effect. The basic work provided a foundation to expand and explore how other combinations and receptor subtypes influenced one another (Bonaventura et al, 2017). The increase in NMDA receptor-mediated responses was obtained by application of SKF 38,393, a D 1 receptor agonist.…”
Section: Dopamine-g Lutamate Inter Ac Ti On S: P Oss Ib Le Influen mentioning
confidence: 99%